The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/09596836221114290
|View full text |Cite
|
Sign up to set email alerts
|

Following the herds? A new distribution of hunting kites in Southwest Asia

Abstract: Remote-sensing analysis of open-source satellite imagery has identified a major, new distribution of undocumented hunting kite structures in northern Arabia. This new data has important implications on the environmental viability of hunting and on possible settlement patterns during the early and middle Holocene. Running across the eastern side of the Nafud Desert in Saudi Arabia, this research has identified star-shaped kites in a distribution that continues on to southern Iraq. From a broader perspective, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Long-term perceptions, memories and beliefs are evident in a range of site types composing the constructed landscape in the Tzuriaz area and elsewhere in the Middle East deserts (e.g. Fradley et al 2022; Haiman 1992; Hill et al 2020; Thomas et al 2021). Examples according to the types of construction and imprint are discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term perceptions, memories and beliefs are evident in a range of site types composing the constructed landscape in the Tzuriaz area and elsewhere in the Middle East deserts (e.g. Fradley et al 2022; Haiman 1992; Hill et al 2020; Thomas et al 2021). Examples according to the types of construction and imprint are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, the kites are huge constructions and larger than any other structures in the desert. It has been suggested that their size and complexity were meant to reflect monumentality, as sometimes they were larger than the functional needs and thus ‘an expression of status, identity and territoriality’ (Fradley et al 2022, 10). The kites were territorial expressions during their use, and the construction of tumuli on them reflects symbolic continuity even after their abandonment as hunting devices.…”
Section: Discussionmentioning
confidence: 99%
“… (A) Map showing the location of Umm Jirsan and key sites mentioned in the text, as well as the range of mustatils and desert kites [ 16 , 17 , 20 , 24 , 27 , 39 ] and (B) pendant tombs (black lines and dots) in the Harrat Khaybar [ 31 ]. (C) Location of newly identified archaeological sites are shown in the inset: (A) stone structures (25.6087 N, 39.7502 E, 25.6020 N, 39.7289 E, and 25.5728 N, 39.7330 E); (B) ‘bow-tie’ shaped structure (25.6091 N, 39.7470 E); (C) lava tube collapse with rock art (25.5879 N, 39.7702 E); and (D) Umm Jirsan D area.…”
Section: Introductionmentioning
confidence: 99%
“… 11 ], and rock art sites [ 12 ], while mobility patterns can be inferred from occupation sites [ 1 , 13 ]. Hunting is evident in the sparse faunal record (see above), and also in the presence of large hunting structures, known as kites [ 14 ]. To date, there is only sporadic evidence of pigment use in northern Arabia.…”
Section: Introductionmentioning
confidence: 99%
“… 15 ]. The use of large-scale traps, which has recently been documented on the north-eastern edge of the Nefud Desert [ 14 , see also 16 ] certainly suggests large quantities of meat may have required processing and preservation to facilitate storage or trade of surplus.…”
Section: Introductionmentioning
confidence: 99%